Basic therapy in the treatment of diffuse fibrocystic mastopathy - I. V. Vysotskaya (Opuholi Ženskoj Reproduktivnoj Sistemy, 2014)
The paper considers the notion of fibrocystic mastopathy and describes its major clinical, morphological, and X-ray manifestations. It re- flects the specific features of the treatment of diffuse fibrocystic mastopathy and presents the most effective drugs used in the therapy of this disease.